Multi-wave analyses of coping, athlete burnout, and well-being among F. A. Premier League academy players - Nicholls, Adam R.; Madigan, Daniel J.; Earle, Keith (Frontiers in Psychology, 2022)
Being a player with an F. A. Premier football academy is very prestigious for young players, but it can also be very stressful too. Coping with stress is particularly important given that one of the undesirable consequences linked to chronic stress is athlete burnout, which may also negatively impact psychological well-being. Understanding the most effective ways to cope with stress, therefore, is important for optimizing academy athlete education. Consequently, the aim of the present study was to examine whether coping predicted changes in athlete burnout, and whether athlete burnout predicted changes in well-being across 14 weeks of the competitive season. A sample of 26, under-18 and under-23, male F.A. Premier academy athletes completed weekly assessments of coping (task-, distraction-, and disengagement-oriented), athlete burnout, and psychological well-being on 14 separate occasions. The results of within-person analyses revealed that task-oriented coping predicted decreases in athlete burnout, which in turn predicted decreased well-being. Teaching high-level academy athletes task-oriented coping strategies may be useful in reducing athlete burnout, which may additionally protect athletes' well-being.